(untitled) (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
Steganography refers to various means of concealing a secret message from view in a digital environment by concealing its visibility so that no one sees it. There are many types of steganography; however, many prefer the use of images and the Least Significant Bit method as it is very simple to use and can hide a great deal of information within an image. In this paper, an efficient LSB-based image steganography technique is designed and implemented to securely hide sensitive information while preserving the visual quality of the original image. The secret information is placed in the least significant bit of each pixel, making the stego image indistinguishable from the original image presented as a cover image. Experimental evaluation using P. S. N. R and M. S.E ensures minimal distortion and high opacity.